THE NUMERACY LITERACY SKILLS OF VISUALLY IMPAIRED STUDENTS - Haslinda, Haslinda; Husniati, Andi; Firdaus, Andi Mulawakkan (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
This study aims to analyze various studies on the numeracy literacy of blind students using the Systematic Literature Review (SLR) approach. The articles analyzed were selected based on inclusion criteria in the form of relevant research in the period 2017–2024, as well as exclusion criteria that include research that is not empirically based or does not focus on blind students. The analysis was conducted using a thematic synthesis approach to group the main findings from the reviewed literature. The results of the study indicate that the numeracy literacy skills of blind students are still below national education standards. The main difficulties they face lie in understanding abstract mathematical concepts, limited access to adaptive learning media, and lack of pedagogical support that suits their needs. Learning strategies that have been proven effective include the use of tactile methods such as jarimatika and braille media, technology-based approaches such as flipped classrooms and digital applications, and contextual learning that involves direct experience. Internal factors such as learning styles and motivation, as well as external factors such as teacher training and environmental support, greatly influence the achievement of numeracy literacy in blind students. This study shows the importance of a systematic and evidence-based approach in developing learning strategies for blind students. Therefore, increasing the accessibility of learning media and training for educators are important steps to create a more inclusive and effective learning environment.